A Literature Survey On Secure De-Duplication Using Convergent Encryption Key Management (International Journal of Engineering and Computer Science, 2014)
One vital challenge of today’s cloud storage services is the management of the ever-increasing quantity of data. To make data management scalable, de-duplication has been a well-known technique to condense storage space and upload bandwidth in cloud storage. Instead of keeping multiple data copies with the same content, de-duplication eliminates redundant data by keeping only one physical copy and referring other redundant data to that copy. Now a day the most arising challenge is to perform secure de-duplication in cloud storage. Although convergent encryption has been extensively adopted for secure de-duplication, a critical issue of making convergent encryption practical is to efficiently and reliably manage a huge number of convergent keys. We first introduce a baseline approach in which each user holds an independent master key for encrypting the convergent keys and outsourcing them to the cloud. However, such a baseline key management scheme generates an enormous number of keys with the increasing number of users and requires users to dedicatedly protect the master keys which is inefficient an unreliable. For that purpose we are going to formally address the problem of achieving efficient and reliable key management in secure de-duplication. We propose Dekey, a new construction in which users do not need to manage any keys on their own but instead securely distribute the convergent key shares across multiple servers.